Ferroptosis-related lncRNAs signature to predict the survival and immune evasion for lung squamous cell carcinoma - Zhang, Rusi; Zhang, Xuewen; Yang, Han; Lin, Yongbin; Wen, Yingsheng; Zhao, Dechang; Chen, Lianjuan; Lin, Peng; Zhang, Lanjun (Frontiers in Genetics, 2022)
Introduction: the investigation on the interactions between ferroptosis and lncRNAs for lung squamous cell carcinoma (LUSC) has been scare, and its impact on tumor immune microenvironment remained unknown. We aim to not only identify a ferroptosis-related lncRNAs signature for LUSC prognosis, but also evaluate its correlation to tumor immune evasion. Methods: RNA sequencing data and survival information were obtained from The Cancer Genome Atlas database. A ferroptosis-related lncRNAs signature (FerRLSig) was developed and validated by univariate Cox regression, Least Absolute Shrinkage and Selection Operator regression and multivariate Cox regression. The tumor immune microenvironment and immune evasion were subsequently evaluated based on the FerRLSig stratification. Results: the FerRLSig consisted of 10 ferroptosis-related lncRNAs and significantly associated with overall survival with satisfactory area under curve (HR= 2.240, 95%CI: 1.845-2.720, P < 0.001, 5-year AUC: 0.756). Based on the FerRLSig stratification, the high-risk group demonstrated significantly higher immune infiltration but also more profound T cell dysfunction and immune evasion, which might ultimately led to the resistance to current immune checkpoint inhibitors. Conclusion: a robust prognostic FerRLSig for LUSC has been developed and validated, demonstrating a close association not only with tumor immune cell infiltration, but also with T cell dysfunction and immune evasion. Further investigation is warranted to better improve the survival of LUSC patients based on the FerRLSig stratification.